Changes in functional vasomotor reactivity in migraine with aura - Wolf, Marc; Jäger, Theodor; Bäzner, Hansjörg; Hennerici, Michael G. (Cephalalgia, 2009)
Migraine with aura (MA) is associated with cerebral hyper- and hypoperfusion during and after the attacks. Several attempts to estimate individual perfusion changes and asymmetries in patients with MA using transcranial Doppler (TCD) have not been consistent. In 70 patients with MA and 40 controls with migraine without aura (MoA) or without any history of migraine, interictally recorded TCD sequences were prospectively analysed. Formal curve analysis of the visually evoked flow response (VEFR) was performed semiautomatically. As a main parameter for functional vasomotor reactivity (fVMR), the visually evoked flow rate (VEFR%) was calculated. The VEFR% showed a significantly higher mean difference of 14.7 ± 12% in MA patients vs. 5.8 ± 4.4% (P < 0.001) in controls. The significant asymmetry of fVMR in MA patients is suggested to reflect interattack persisting vasomotor changes which are of pathophysiological interest and may be used as a monitoring tool under prophylactic medication.
Gesehen am 17.03.2021